Stimulant Medications and Cognition, Behavior and Quality of Life in Children and Youth with HIV. Issue 1 (January 2016) - Sirois, Patricia A.; Aaron, Lisa; Montepiedra, Grace; Pearson, Deborah A.; Kapetanovic, Suad; Williams, Paige L.; Garvie, Patricia A.; Nozyce, Molly L.; Malee, Kathleen; Nichols, Sharon L.; Kammerer, Betsy L.; Mitchell, Wendy G.; et al.
Abstract : Background: Limited empirical investigation exists into longitudinal changes in cognition, behavior or quality of life (QOL) in children with perinatal HIV who are prescribed stimulants. Methods: This study was an analysis of longitudinal data from children age 3–19 years, with perinatal HIV infection, with and without prescriptions for stimulant medications [prescription (PG) and comparison (CG) groups, respectively], matched on age, availability of CD4% and outcome measures of cognition, behavior and QOL. Generalized estimating equation models were used to evaluate effects of stimulant exposure on change in measured outcomes over 3 years of follow-up, adjusting for baseline levels of outcomes and relevant covariates. Results: Children in both the PG (n = 132) and the CG (n = 392) obtained mean verbal and performance (nonverbal) intelligence quotients (VIQ and PIQ, respectively) in the low-average range for age. At baseline, those in PG demonstrated more frequent signs of hyperactivity, impulsivity and conduct and learning problems than those in CG ( P ⩽ 0.003 in unadjusted analyses). At follow-up, after adjustment for baseline functioning and other relevant covariates, there were no significant changes from baseline in VIQ or PIQ. Stimulant prescription use, however, was associated with worsening symptoms of hyperactivity ( P = 0.01), impulsivity ( P = 0.04), learning problems ( P < 0.001) and worsening of perceived health status ( P < 0.001). Conclusions: The results suggest expectations for behavioral improvement may not align well with long-term effects of stimulant prescription use on behavior and QOL in children with HIV. Further research is necessary to determine if there are subsets of children who may benefit from stimulant therapy. Abstract : Supplemental Digital Content is available in the text.